2010
DOI: 10.1115/1.4001886
|View full text |Cite
|
Sign up to set email alerts
|

Outflow Conditions for Image-Based Hemodynamic Models of the Carotid Bifurcation: Implications for Indicators of Abnormal Flow

Abstract: Computational fluid dynamics (CFD) models have become very effective tools for predicting the flow field within the carotid bifurcation, and for understanding the relationship between local hemodynamics, and the initiation and progression of vascular wall pathologies. As prescribing proper boundary conditions can affect the solutions of the equations governing blood flow, in this study, we investigated the influence to assumptions regarding the outflow boundary conditions in an image-based CFD model of human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 57 publications
4
84
0
Order By: Relevance
“…3 On the other hand, hemodynamic indicator such as helical flow index was proposed to reveal the global organization of blood flow, which was calculated from a Lagrangian-based method for helical flow quantification based on the velocity data from either computational fluid dynamics or phase contrast magnetic resonance imaging. 33,34,68,69,71,72 Through simulating the blood flow in an idealized model of aortocoronary bypass, Morbiducci et al found a linear inverse relationship between the oscillating shear index (a well-known risk index for atherogenesis) and the HFI. 51,71 Furthermore, based on hemodynamic simulations data of 50 carotid bifurcations, Gallo et al 33 demonstrated that the exposure of each carotid bifurcation to disturbed flow measured by time-averaged wall shear stress, oscillatory shear index and relative residence time decreased as the timeaveraged value of the absolute value of helicity increased.…”
Section: Clinical Diagnosis Of Artery Statusmentioning
confidence: 98%
“…3 On the other hand, hemodynamic indicator such as helical flow index was proposed to reveal the global organization of blood flow, which was calculated from a Lagrangian-based method for helical flow quantification based on the velocity data from either computational fluid dynamics or phase contrast magnetic resonance imaging. 33,34,68,69,71,72 Through simulating the blood flow in an idealized model of aortocoronary bypass, Morbiducci et al found a linear inverse relationship between the oscillating shear index (a well-known risk index for atherogenesis) and the HFI. 51,71 Furthermore, based on hemodynamic simulations data of 50 carotid bifurcations, Gallo et al 33 demonstrated that the exposure of each carotid bifurcation to disturbed flow measured by time-averaged wall shear stress, oscillatory shear index and relative residence time decreased as the timeaveraged value of the absolute value of helicity increased.…”
Section: Clinical Diagnosis Of Artery Statusmentioning
confidence: 98%
“…To achieve this goal, we applied the consolidated approach of coupling a three-dimensional vascular model, where local information is needed, to a reduced-order model representing the downstream vasculature. 4,15,16,36,41,48,52,60 In this way, more realistic adaptive boundary conditions can be derived because through-scale models work together in order to accommodate the complex interaction between the phenomena modeled by each subcomponent of the whole system. For the sake of comparison, we also imposed, in the same isolated model of carotid bifurcation, three different fixed flow rate redistributions of the inlet common carotid artery (CCA) flow rate between the internal and external carotid arteries (ICA and ECA, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors assessed the sensitivity of image-based CFD studies within the carotid bifurcation. 14,31,41,46,47,59,61 All of the authors focused their analyses on the sensitivity of WSS-based metrics.…”
Section: Introductionmentioning
confidence: 99%
“…For each bifurcation analysis, subject-specific velocity boundary conditions were prescribed at CCA inlet and ICA outlet using Womersley velocity profiles derived from pulsatile spectral waveforms obtained by pulsed Doppler and traction-free boundary condition was defined at ECA outlet [9,[26][27][28]. Figure 3 presents the volume hexahedral mesh (left) and the distal CCA velocity waveform (right) used for solving the hemodynamics of subject P1.…”
Section: Blood Flow Modelmentioning
confidence: 99%